LEGAL TRANSPLANTATION, REFORMATION MOVEMENT, AND MODEL FOR JUDGE MADE LAW IN INDONESIA - Ade Saptomo (UNTAG Law Review, 2017)
Before reformation, there are as many as 38 articles of Code Penal of Indonesia repealed by acts. After reformation movement 1998, Indonesian statelegal policy has been changed by many approaches, for instance, from centralization to decentralization, top down to bottom up approach, etic to emic perspective. The main legal research question: why did the legal policy change? What's the legal implication? Which articles of Code Penal have been repealed after changing such approach? To answer it, social legal research has been done. Theoretically, the good law is not separated from its social norms and culture norms where it's existence. In the sense of public law, good public law must accommodate to the social norms and culture norms as recommended by Friedman's concept that law (judicial decision) as product of system (legal substance, legal structure, legal culture). Legal culture itself means Indonesian-social and cultural forces. The results of research is below: (1) not all legal transplantation can't be retained but must be repealed in accordance with Indonesian social-cultural character; (2) to make the good legal substance, judge made law should accommodate social and cultural forces; (3) after new approach, there are 2 (two) articles of Code Penal repealed by and 15articles of Code Penal appealed to Constitutional Court Decision. Its recommendation, in the decision making process, law should accommodate the Indonesian social and cultural forces.